The Old Royal Palace in Athens and the Greek National Idea - Petrunina, Olga E. (Actual Problems of Theory and History of Art, 2020)
The paper explores the process of forming the ensemble of the Old Palace in Athens in the 19th‑20th centuries in connection with the development of the Megale Idea — the Greek national idea, which gradually became the state ideology of the Greek Kingdom. From the very beginning, the Royal palace as the residence of the chief of state was considered a visual symbol of the diachronic unity of the Greek ethnos. Its location, architectural design and interior decoration served this aim. The financial difficulties of the newborn Greek state hindered the architects in their efforts to complete the project of the palace. Nevertheless, the author of the final project F. Gärtner and the German artists who worked on the interiors managed to demonstrate maintaining continuity between the ancient Hellenes and the modern Greeks. The foundation of a palace chapel emphasized the continuity between Byzantine and modern Greeks. The construction of the Tomb of the Unknown Soldier and the transformation of the palace into the residence of the national parliament seemed to be significant stages of the evolution of the ensemble. They did not change the general ideological attitude of the palace, but supplemented it with new content focusing on national values such as democracy and the struggle for independence. The latest additions to the palace ensemble, emphasizing these values, have been made in our time.
Keywords: Greek Revival architecture; Modern Greek art; Megale Idea; Modern Greek studies; Modern Greek history